USULAN RANCANGAN TATA LETAK TEMPAT PEMBUANGAN SAMPAH (TPS) DI PASAR TRADISIONAL KOTA BATAM - Nofriani Fajrah; Sri Zetli; Ummi Kalsum (Universitas Putera Batam, 2019)
The market as one of the public facilities that are needed by the community in economic activity. But at present, the conditions in traditional markets are very dirty, smelly and unhygienic. This is caused by ineffective waste disposal management. The purpose of this research is to design a proposed layout of an effective Waste Disposal Site in the traditional market of Batam City, Pasar Toss 3000 Batam. This study uses the Activity Relationship Chart and Activity Relationship Diagram methods to obtain an effective Waste Disposal Site layout for the stalls of traders. Based on the results of this research, it can be seen that the design of the layout of the Waste Disposal Site for the traders' stalls is influenced by the criteria of proximity needs. This shows that the layout of the Waste Disposal Site must be close together according to the needs of each type of seller’s product. Based on the results of the proposed design, the layout of the Waste Disposal Site is arranged based on the needs of traders in accordance with the type of seller’s product.